Treu ist das Wort: zur Theologie des Ordo bei Karl Rahner - Scheuer, Manfred (Zeitschrift für katholische Theologie, 2004)
Rahner positions sacramental Orders between an existential ecclesiology, arising from the individual vocation and its pneumatological integration in the church, and an essential ecclesiology, arising from God's irreversible self-communication in history. During the 1950s preaching the word and celebrating the eucharist are for Rahner the central focus of priestly existence. With Vatican II the sacramentality of the church, Rahner's understanding of the ius divinum and a more positive appreciation of the world and society become weightier emphases. His indirect method is informed by concrete social and ecclesial developments. Questions of freedom, authority and emancipation, of democracy and social issues, and the growing importance of communities and basic christian communities influence Rahner's understanding of orders.